2017
DOI: 10.20319/pijss.2017.32.14871499
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Perceived Writing Difficulties Through the Social Cognitive Theory

Abstract: Writing can both be considered as social and cognitive activity. Nevertheless

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…However, considering that frequent difficulty, it would probably be positive for the students, a future modification of the template for to reinforce the guide (instructions and recommendations) in all the chapters, but especially in those highlighted by the students as the most difficult (Tables 4 and 5 ). Although these difficulties are not exclusive to students of scientific areas (Maznun et al, 2017 ; Rahmat et al, 2017 ), for these students the composition strategy, seen as a “thinking” process where the writer dedicates as much attention to the content as well as to composing it, is less prevalent than in non-scientific writers (Brown, 2001 ). Here the role of the instructors is very relevant since this difficulty entails a greater margin for learning and work of this skill, which can be facilitated with adequate support.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering that frequent difficulty, it would probably be positive for the students, a future modification of the template for to reinforce the guide (instructions and recommendations) in all the chapters, but especially in those highlighted by the students as the most difficult (Tables 4 and 5 ). Although these difficulties are not exclusive to students of scientific areas (Maznun et al, 2017 ; Rahmat et al, 2017 ), for these students the composition strategy, seen as a “thinking” process where the writer dedicates as much attention to the content as well as to composing it, is less prevalent than in non-scientific writers (Brown, 2001 ). Here the role of the instructors is very relevant since this difficulty entails a greater margin for learning and work of this skill, which can be facilitated with adequate support.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of negative thoughts about L2 writing or perceived difficulties regarding L2 writing had a significant impact on L2 writers’ ability to convey their ideas in writing 42 , thus influenced their writing performance. In addition to other factors, writing instructors concurred that students’ perception of difficult with EFL academic writing was a contributing factor to their poor writing performance 43 . Despited the negative influece of writing difficulty perception on writing performance, Wei and Zhang 44 found that the degree of difficulty that L2 writers perceive in L2 writing could be indicative of their awareness of the inadequacy of their L2 writing knowledge or their uncertainty about the L2 writing process.…”
Section: Literature Review and Research Modelmentioning
confidence: 96%
“…Hence, these studies propose that educators and curriculum designers should take into account the aforementioned factors when developing strategies and interventions to support ESL learners in improving their writing abilities. Even in Malaysia, recent research has explored ESL learners' writing difficulties through social cognitive theory Rahmat et al (2017) as well as the psychology of audience awareness in the writing composing process (Rahmat et al, 2018). These two studies apply psychological theories to the context of ESL learners' writing difficulties and contribute to a deeper understanding of the challenges ESL students face in the writing process and can inform strategies for improvement.…”
Section: Statement Of Problemmentioning
confidence: 99%